Phenotypic plasticity of the basidiomata of Thelephora sp. (Thelephoraceae) in tropical forest habitats - Itzel Ramírez-López; Margarita Villegas Ríos; Zenón Cano-Santana (Revista de Biología Tropical, 2013)
Phenotypic plasticity in macroscopic fungi has been poorly studied in comparison to plants or animals and only general aspects of these changes have been described. In this work, the phenotypic variation in the basidiomata of Thelephora sp. (Thelephoraceae) was examined, as well as some aspects of its ecology and habitat, using 24 specimens collected in the tropical forests of the Chamela Biological Station, Jalisco, Mexico. Our observations showed that this taxon has clavarioid basidiomata that can become resupinate during development and growth if they are in contact with rocks, litter or live plants, establishing in the latter only an epiphytic relationship. This tropical species may form groups of up to 139 basidiomata over an area of 32.2m2, and in both types of vegetation (tropical sub-evergreen and deciduous forest) were primarily located on steep (>20°) South-facing slopes. It is found under closed canopy in both tropical forests, but its presence in sub-evergreen forests is greater than expected. La plasticidad fenotípica en hongos macroscópicos ha sido poco estudiada en comparación con la de plantas o animales y solo se conocen aspectos generales de estos cambios. En este trabajo se examinó la variación fenotípica en los basidiomas de una especie de Thelephora sp. (Thelephoraceae), así como algunos aspectos de su ecología y hábitat a partir del estudio de 24 ejemplares recolectados en bosques tropicales de la Estación de Biología de Chamela, Jalisco, México. Nuestras observaciones mostraron que este taxon presenta basidiomas en forma clavarioide, los cuales pueden modificarse a resupinados si en su proceso de desarrollo se interponen obstrucciones físicas como rocas, restos vegetales o plantas vivas, estableciendo en estas últimas solo una relación epifítica. Esta especie llega a formar conjuntos de hasta 139 basidiomas en un área de 32.2m2; con localización predominante en laderas orientadas hacia el sur, de pendientes mayores a 20°, bajo doseles cerrados y con presencia mucho más significativa de lo esperado en el bosque tropical subperennifolio.